INTERCULTURAL COMPETENCE AS A COMPONENT OF PERSONALITY DEVELOPMENT : THEORETICAL ASPECT - Лучевич, Виктория; Вайдич, Татьяна (SWorldJournal, 2020)
The article deals mith the concept of “intercultural competence” and its role in intercultural interaction. A special role is paid to the peculiarities of the authors’ interpretations of this concept. The stages of formation of the individual intercultur